2017
DOI: 10.1002/cctc.201700494
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of 2‐Arylquinazoline Halidoruthenacycles in Arylation Reactions

Abstract: The synthesis of a range of new cyclometallated organoruthenium(II) complexes through the ortho‐C−H activation of the aryl group in 2‐aryl‐substituted quinazolines with [RuX2(p‐cymene)]2 is described. The beneficial effect of the carboxylate ligand on both the cyclometallation and the further arylation reaction step was demonstrated. Mechanistic studies reveal that bromide and iodide anions decelerate the arylation process by an in situ ligand exchange reaction. Additionally, a detailed NMR spectroscopy invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Arene-free catalysts for C-H functionalisation are widely known, such as recent examples from the groups of Larrosa 43 and Frost; 11 Štefane profiled the release of p-cymene during a prototypical C-H arylation reaction. 40 The present study demonstrates that not only are arene-free complexes more reactive than arenecontaining catalysts, but that arene-containing catalysts are ineffective for C-H arylation reactions. This is important given the preponderance of arene-containing ruthenium complexes in the C-H functionalisation literature, 15 despite the demonstrated competence of alternative precursors such as [RuH2(CO)(PPh3)3], 46 [RuH(COD)2][BF4], 47 and even RuCl3.nH2O [48][49][50][51] in C-H arylation reactions; in addition, arenefree ruthenium carboxylate complexes and even ruthenium alkylidenes have been deployed in C-H alkylation reactions.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 61%
See 1 more Smart Citation
“…Arene-free catalysts for C-H functionalisation are widely known, such as recent examples from the groups of Larrosa 43 and Frost; 11 Štefane profiled the release of p-cymene during a prototypical C-H arylation reaction. 40 The present study demonstrates that not only are arene-free complexes more reactive than arenecontaining catalysts, but that arene-containing catalysts are ineffective for C-H arylation reactions. This is important given the preponderance of arene-containing ruthenium complexes in the C-H functionalisation literature, 15 despite the demonstrated competence of alternative precursors such as [RuH2(CO)(PPh3)3], 46 [RuH(COD)2][BF4], 47 and even RuCl3.nH2O [48][49][50][51] in C-H arylation reactions; in addition, arenefree ruthenium carboxylate complexes and even ruthenium alkylidenes have been deployed in C-H alkylation reactions.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 61%
“…In contrast, other studies have revealed two-phase Hammett plots with ρ ≈ 0.4 where σp < 0 and ρ < 0 where σp > 0. 40,41 In attempts to probe the latter step experimentally, we prepared known complexes 42 of the same structure as III and exposed these to aryl halides in toluene solution, and monitored reactions by 1 H NMR or UV/visible spectroscopy. Unfortunately, oxidative addition did not occur.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 99%
“…All of the chemicals and organic solvents were purchased from commercial suppliers and used without further purification. [Cp*Ir(OAc) 2 ], [Cp*Rh(OAc) 2 ], [( p ‐cymene)Ru(OAc) 2 ], and 2‐(3,5‐dimethylphenoxy)pyridine were synthesized by modification of literature methods. Thin‐layer chromatography was performed with Merck (Darmstadt, Germany) silica gel 60 (F‐254, 0.25 mm).…”
Section: Methodsmentioning
confidence: 99%
“…A great number of them are based on nitrogen as the metal-coordinating atom, the pyridine ring being prevalent, although other azaheterocycles, such as pyrazole, oxazoline, and quinoline have also been successfully employed in transition-metal-catalyzed ortho-C-H bond functionalization [33]. Požgan and co-workers have demonstrated that the quinazolinyl [34,35] and pyrimidinyl [36] groups efficiently allow regioselective ortho-arylations in the presence of Ru(II)-carboxylate catalyst, even in water as the solvent in some cases [37,38]. The success of Ru(II) catalysts is most likely ascribed to the easy formation of ruthenacyclic intermediate stable in water via C-H bond deprotonation with the assistance of directing groups [35,37,[39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, many synthetic methods for the construction of pyrazine derivatives have been developed [58][59][60][61][62][63], yet there is still great demand for the generation of novel pyrazine libraries. As a part of our ongoing interest in metal-catalyzed functionalization of (hetero)arenes via C-H bond activation [34][35][36][37][38], we reasoned that a pyrazine nucleus could direct cleavage and further functionalization of ortho-C-H bonds of the benzene ring in phenyl-substituted pyrazines. Moreover, by using 2,3-diphenylpyrazines as substrates, both nitrogen atoms could cooperate with the catalytic metal center to hypothetically promote four ortho-C-H bond activations, thus enabling the construction of highly functionalized, especially arylated or π-conjugated pyrazine derivatives.…”
Section: Introductionmentioning
confidence: 99%